AB0819 Bone Mineral Density in Postmenopausal Women with Hypertension. (10th June 2014) - Vele, P.; Simon, S.-P.; Muntean, L.; Fodor, D.; Rednic, S.
Abstract : Background: Osteoporosis and hypertension are two major age-related disorders. The underlying molecular mechanism for these two conditions is not known. Some studies showed that the renin-angiotensin system, which pays a central role in the control of blood pressure also accelerate bone resorbtion. Objectives: The aim of this study was to examine the relationship between hypertension and bone mineral density (BMD) among postmenopausal women. Methods: One hundred postmenopausal women attending in the Rheumatology Clinic, Cluj-Napoca, Romania, for osteoporosis evaluation were included in this study. Informed consent was obtained from all participants. Women treated with anti osteoporotic medication, secondary causes of osteoporosis and medication known to interfere with bone metabolism were excluded. The characteristics studied included age, body weight, height, body mass index (BMI), presence of hypertension, age of menarche, age of menopause, age since menopause and BMD. BMD was assessed by dual-energy X ray absorptiometry (DXA) at lumbar spine (L2-L4) and proximal femur (given as g/cm 2 and as T-score values). Hypertension was defined by blood pressure data and/or use of antihypertensive medication. Results: Women were placed into two groups according to the presence of hypertension. According to WHO criteria for BMD patients were divided into three groups: with normal BMD, osteopenia and osteoporosis. The mean age of patients was 67.56±0, 76 years, 73% had hypertension. Hypertensive women were older (68.18±68 vs. 64.65±72, p=0.06), had higher values of BMI (33.08±83 vs. 26.19±21, p=0.009), higher menopausal age (48.44±13.02 vs. 46.76±31.23, p=0.08) and longer postmenopausal age (21.46±10.1 vs. 19.51±25, p=0.55) then women without hypertension. BMD at spine (-1.25±3.37 vs. -2.22±1.95, p=0.01), trochanter (-0.98±1.44 vs. -1.5±1.77, p=0.04) and femoral neck (-1.51±0.98 vs. -1.8±1.34, p=0.2) was higher in women with hypertension. Hypertension was found in 17 (54.84%) patients in the osteoporosis group, 33 (80.49%) in the osteopenia group and respectively 23 (82.14%) in normal BMD group (p=0, 05). In our study the presence of hypertension was higher in non-osteoporotic patients (osteopenia and normal BMD). The multivariate analysis identified higher age, weight and longer postmenopausal age as independent factors associated with both hypertension and lower BMD. Conclusions: BMD was higher in non-hypertensive patients. The majority of the patients were non osteoporotic. Higher age, weight and longer postmenopausal age were identified as independent factors associated with hypertension and lower BMD. References: Ilić K, Obradović N, Vujasinović-Stupar N. The relationship among hypertension, antihypertensive medications, and osteoporosis: a narrative review. Calcif Tissue Int. 2013 Mar;92(3):217-27. Yazici Selma, Yazici M, Korkmaz M, Erkan M, Baki Z, Erden I. Relationship between blood pressure levels and bone mineral density in postmenopausal Turkish women. Arch Med Sci. 2011 April; 7(2): 264–270. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5234